Isolation and expression of hemolysin e (hlye) from salmonella enterica serovar typhi (s. typhi) isolates - A. Rahman @ Rahim, Rasyada (2014)

(untitled)
Comparative proteomic analysis of Salmonella enterica serovar Typhi (S. Typhi) and Salmonella enterica serovar Typhimurium (S. Typhimurium) revealed a subset of highly expressed proteins unique to S. Typhi. One of these proteins is hemolysin E (HlyE). The hlyE gene is necessary for human-host specificity, which is absent or functionally altered in S. Typhimurium. hlyE gene belongs to Salmonella Pathogenecity Island (SPI) 18. In this study, the presence and the function of hlyE gene in S. Typhi clinical isolates was determined. PCR and DNA sequence analyses showed that S. Typhi, serovar that is specific for human, harbors an intact copy of hlyE gene. Despite the presence of hlyE gene in S. Typhi isolates, the bacteria did not display haemolytic activity when cultured on horse blood agar plates. Increased haemolytic activity was observed when S. Typhi was grown on horse agar plates in disk-diffusion assay in the presence of ampicillin disk. Crude periplasmic proteins extracted from S. Typhimurium and S.Typhi (vaccine strain and clinical isolates) showed the presence of 34 kDa proteins, which is an expected size for HlyE. The crude protein extracts from S. Typhi showed strong haemolytic activity on the blood agar plates. HlyE recombinant protein showed positive reaction against IgG of sera from typhoid patients, suggesting reactive HlyE production during infection. The purified HlyE recombinant proteins have a cytotoxic activity towards U937 human monocytic cell line. This research provides fundamental information on the activity of hlyE gene product and contributes additional knowledge in the study of S. Typhi pathogenesis in human.